Kasvua hillitsevien aineiden vaikutus pavun taimien kasvuun IV. Vaikutusasteen riippuvuus valo-oloista - Kaukovirta, Erkki (Agricultural and Food Science, 1970)
The intensity of growth retardation of B-nine, Cycocel and Phosfon at three levels of light intensity (100 % = 26000 lux = 2100 μW in spectral band from 400 to 800 nm, 50 % and 23 %) was studied in experiments carried out in growth chambers equipped with WHO 110 Watt fluorescent tubes. In addition, the effect of near UV-light and incandescent light on the growth retarding activity of Phosfon and Cycocel were compared to their effect in darkness and in natural daylight. Philips HPW 125 W lamps were used as a source of near UV-light. One HPW 125 W lamp and two 60 W incandescent lamps were placed to cover the area of 1 m2, and the distance from lamps to plants was 70 cm. The duration of the light period was 8 hours. Seeds of Phaseolus vulgaris var vulgaris were pregerminated at 25° C and then grown in 4" plastic pots in sand at 18° C average night and 21° C day temperatures and in experimental light conditions. When the primary leaves were fully opened the plants were treated with growth retardants. The amount of Cycocel and B-nine in the treatments was 100 mg and that of Phosfon 15 mg of active compound per pot of two seedlings. The pots were irrigated by modified (WENT 1957) Hoagland solution (0.02 %) daily. Leaf temperatures were measured on four successive days 4 hours after the beginnig of the light period by using thermocouples fastened to the leaves from below. Stem length, leaf area (by optical leaf planimeter) and fresh and dry weights were measured before the application of retardants, and 10 days after the application. From these data the net assimilation rates (NAR) were calculated by using the formula of GREGORY (1926). The dry weights of roots were not included. The results are given in Tables 1—2 and in Figures 1—2. The percentages of stem growth retardation of B-nine, Cycocel and Phosfon were practically the same at all light intensities studied. The increase of fresh and dry weight of seedlings was restricted most by all retardants at 23 % level of light intensity. Increase in leaf temperature caused by the increase in the energy within the spectral band from 400 to 800 nm did not affect the intensity of stem growth retardation. If the leaf temperature was increased without any increase in the light intensity, the effectiveness of B-nine and Cycocel, but not that of Phosfon, in restricting stem growth decreased. The amount of Cycocel used in the experiments retarded the stem growth by 27 % in natural daylight, but stimulated it in near UV-light, in incandescent light and in darkness respectively by 20, 23 and 6 %. Phosfon inhibited the stem growth by 42 % in natural daylight, by 32 % in near UV-light, but significantly less in darkness (by 6 %) and in incandescent light (by 2 %). The NAR of treated plants was greater than that of untreated at 100 %-level of light intensity, but not at lower light intensities. Cycocel and Phosfon reduced the NAR in incandescent light, Phosfon more pronouncedly than Cycocel. The fresh and dry weights of seedlings treated with Cycocel or Phosfon increased in darkness, but not those of untreated plants. In other light treatments, Phosfon reduced the fresh weight independently of the light quality, but Cycocel only in natural day light. It is suggested that the differences in plant response to growth retardants in winter and in summer are caused, at least partly, by the seasonal variations in the quality of natural daylight.